2020
DOI: 10.1007/s00253-020-10710-z
|View full text |Cite
|
Sign up to set email alerts
|

T cell immunity rather than antibody mediates cross-protection against Zika virus infection conferred by a live attenuated Japanese encephalitis SA14-14-2 vaccine

Abstract: Zika virus (ZIKV) and Japanese encephalitis virus (JEV) are closely related to mosquito-borne flaviviruses. Japanese encephalitis (JE) vaccine SA14-14-2 has been in the Chinese national Expanded Program on Immunization since 2007. The recent recognition of severe disease syndromes associated with ZIKV, and the identification of ZIKV from mosquitoes in China, prompts an urgent need to investigate the potential interaction between the two. In this study, we showed that SA14-14-2 is protective against ZIKV infect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…It has been shown in Dengue virus infection, efficient CD8 T cells response is sufficient to inhibit ADE in infected mice. Our present study together with previous findings (18,24) all suggest that cross-reactive JEV-specific CD8 T cells are protective to ZIKV infection in wild-type mice that are not HLA-transgenic (18,19,25). Thus, JEV vaccine can be clinically used for the prevention of ZIKV infection and also is at low risk of ADE induction in immune-competent humans.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It has been shown in Dengue virus infection, efficient CD8 T cells response is sufficient to inhibit ADE in infected mice. Our present study together with previous findings (18,24) all suggest that cross-reactive JEV-specific CD8 T cells are protective to ZIKV infection in wild-type mice that are not HLA-transgenic (18,19,25). Thus, JEV vaccine can be clinically used for the prevention of ZIKV infection and also is at low risk of ADE induction in immune-competent humans.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies by us and others have independent shown that antibodies against JEV are cross-reactive to ZIKV, but passive transfer of JEV antisera fails to protect ZIKV infection in Ifnar1 −/− mice (18,24). Thus, antibody response is unlikely to mediate the protection of JEV vaccine-immunized HLAtransgenic or non-transgenic Ifnar1 −/− mice from ZIKV infection.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We found that T cell responses triggered by pre-existing dengue virus infection are protective against Zika virus infection [ 68 ]. In a mouse model, specific T cells to Japanese encephalitis virus, another flavivirus, could also protect against Zika [ 69 ].…”
Section: Investigating Neurological Complications Of Zika In Adolesce...mentioning
confidence: 99%
“…2020 ). Importantly, it has recently been demonstrated that the T-cell response following immunization with a live-attenuated JEV vaccine, produced a cross-protection against ZIKV infection in humans ( Wang et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%